Pengetahuan dan Sikap Masyarakat dalam Upaya Pencegahan Penyakit Tuberkulosis Paru: Tinjauan Pustaka - Radandima, Ester; Toru, Veronika; Mila, Antonetha R H (JURNAL KESEHATAN PRIMER, 2022)
Background:  Pulmonary Tuberculosis is a major cause of death in most countries in the world. Lack of information obtained by the public can affect public knowledge in making efforts to prevent the transmission of pulmonary tuberculosis. If this is left unchecked, it will have a bad impact in the form of increasingly widespread transmission of pulmonary tuberculosis and increasing morbidity rates resulting in increased deaths. Objective: to determine community knowledge and attitudes in efforts to prevent pulmonary TB disease. Method: The research used a literature review with problem identification stages, data search using the Google Scholar database with the keywords "Community Knowledge and Attitudes in Efforts to Prevent Pulmonary Tuberculosis". Then screening is carried out according to the criteria for annual journal publication limits for the last 5 years, original article type, the journal can be accessed in full text in the form of national journal articles. The following stages are summarizing and analyzing data using PICO, these stages are depicted in a prism chart. Results: using a Literature Review study based on 10 Journal Articles, there are 7 journals that have good knowledge, 3 journals that have sufficient knowledge in efforts to prevent Lung Tuberculosis, then there are 8 journal articles that have a good attitude and there is 1 journal article that has sufficient knowledge in efforts to prevent the disease Pulmonary Tuberculosis.